Peritumoral brain edema in angiomatous supratentorial meningiomas: an investigation of the vascular endothelial growth factor A pathway. Issue 11 (11th February 2013) - Nassehi, Damoun; Sørensen, Lars P.; Dyrbye, Henrik; Thomsen, Carsten; Juhler, Marianne; Laursen, Henning; Broholm, Helle
Abstract : The aim of this work was to study the vascular endothelial growth factor A (VEGF‐A) pathway and peritumoral brain edema (PTBE) through comparison of non‐angiomatous and angiomatous meningiomas. Meningiomas are common intracranial tumors, which often have PTBE. VEGF‐A is an integral part of PTBE formation and angiogenesis, and the capillary‐rich angiomatous meningiomas are known for their PTBE. The VEGF‐A receptor VEGFR‐2 is responsible for the angiogenic effect of VEGF‐A on endothelial cells, which is enhanced by the co‐receptor neuropilin‐1. Forty non‐angiomatous, 22 angiomatous meningiomas, and 10 control tissue samples were collected for the study. Magnetic resonance images were available for 40 non‐angiomatous and 10 angiomatous meningiomas. Tissue sections were immunostained for CD34, MIB‐1, estrogen‐ and progesterone receptors. ELISA, chemiluminescence, and RT‐qPCR were used for VEGF‐A, VEGFR‐2, and neuropilin‐1 protein and mRNA quantification. Angiomatous meningiomas had larger PTBE (695 vs 218 cm 3, p  =  0.0045) and longer capillary length (3614 vs 605 mm/mm 3, p  <  0.0001). VEGF‐A mRNA, neuropilin‐1 mRNA, and VEGFR‐2 protein levels were higher in angiomatous meningiomas independently of the capillary length (p  <  0.05). Neuropilin‐1 protein levels were lower in angiomatous meningiomas (p  <  0.0001). The VEGF‐A pathway and tumor capillary length may be essential for PTBE‐formation in meningiomas. Further investigations of this pathway could lead to earlier therapy and targeted pharmacological treatment options.